Micropropagation of F1 hybrid brinjal (Solanum melongena L.) - Mohamad Nazir, Nurelia Azian (2014)
This study was conducted to determine the best concentration of 6-benzylaminopurine (BAP) or kinetin on shoot multiplication from shoot tip explant of F1 hybrid brinjal (Solanum melongena). The shoot tips derived from germinated seedling were used as explants and cultured on half strength Murashige and Skoog (MS) medium supplemented with different BAP or kinetin concentration. This experiment was carried out at the Tissue Culture Laboratory, Department of Agriculture Technology, Universiti Putra Malaysia, Serdang. Seven cytokinin treatments were used in this experiment which were 0.0, 1.0, 2.0, 5.0 mg/L BAP and 1.0, 2.0, 5.0 mg/L kinetin. The experiment was conducted using Completely Randomized Design (CRD) with 10 replications per treatment and 10 explants in each replication. It was observed that the medium containing 1.0 mg/L kinetin induced the highest mean number of shoots per explants (0.91) after 5 weeks of culture but was not significantly different compared with the control treatment and other BAP and kinetin treatments. The highest mean number of shoots (0.92) proliferated after 3 weeks of subculture was on medium supplemented with 1.0 mg/L BAP but also showed no significant difference compared with the control treatment as well as other BAP and kinetin treatments except 1.0 mg/L kinetin which showed a significant reduction on mean number of shoots formed per explant.